2015
DOI: 10.1111/tri.12675
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of mitochondrial aldehyde dehydrogenase-2 induces liver injury via activation of the mitogen-activated protein kinase pathway

Abstract: SummaryThe aim of this study was to determine the role of ALDH2 in the injury of liver from brain-dead donors. Using brain-dead rabbit model and hypoxia model, levels of ALDH2 and apoptosis in tissues and cell lines were determined by Western blot, flow cytometry (FCM), and transferase (TdT)-mediated biotin-16-dUTP nick-end labeling (TUNEL) assays. After the expression of ALDH2 during hypoxia had been inhibited or activated, the accumulations of 4-hydroxynonenal (4-HNE) and molecules involved in mitogen-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…This effect has been suggested to occur through the inhibition of Akt, which increases the Bax/Bcl-2 ratio and activates a caspase-3 apoptotic cascade[ 43 , 44 ]. This Akt inhibition in the presence of 4-HNE can be totally reversed by using an ALDH2 agonist, such as Alda-1[ 45 ]. Further investigations have evidenced that increased ALDH2 expression through Alda-1 treatment protects I/R-induced brain cell necrosis and apoptosis[ 16 , 24 ].…”
Section: Aldh2: Necroptosis and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…This effect has been suggested to occur through the inhibition of Akt, which increases the Bax/Bcl-2 ratio and activates a caspase-3 apoptotic cascade[ 43 , 44 ]. This Akt inhibition in the presence of 4-HNE can be totally reversed by using an ALDH2 agonist, such as Alda-1[ 45 ]. Further investigations have evidenced that increased ALDH2 expression through Alda-1 treatment protects I/R-induced brain cell necrosis and apoptosis[ 16 , 24 ].…”
Section: Aldh2: Necroptosis and Apoptosismentioning
confidence: 99%
“…Besides these benefits of ALDH2 observed in the heart and brain, benefits have also been shown for limiting neuronal apoptosis in spinal cord IRI[ 24 ]. Recently, Zhong et al[ 45 ] reported that low ALDH2 promotes liver apoptosis through the MAPK pathway when ALDH2 agonists are used, in which ALDH2 action is not only based on the 4-HNE clearance ratio, but also on its subsidiary involvement in controlling indirect 4-HNE pathways.…”
Section: Aldh2: Necroptosis and Apoptosismentioning
confidence: 99%
“…Several studies described that 4-HNE was regulated by c-Jun N-terminal protein kinase (JNK) indirectly, which functioned like signaling molecules, or directly by the kinase's active domains. JNK modulated the rate of cells and mediated neuronal injury in different ischemic models [51,52]. Since 4-HNE is a substrate of ALDH2, it is reasonable to hypothesize that ALDH2 mediates JNK activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the activity change is not timely for the oxidation of acetaldehyde to acetic acid, the damage to the liver cells will be more serious compared with ethanol. If ADH activity is inhibited, the ethanol hazard for the body itself will increase (28,29). ALDH is also an important enzyme in ethanol metabolism, as it can transform toxic acetaldehyde associated with alcoholic liver injury into acetic acid, which is a nontoxic metabolic product.…”
Section: Discussionmentioning
confidence: 99%